ANALISIS INTERFERENSI BAHASA JAWA PADA BAHASA INDONESIA DALAM INTERAKSI BELAJAR MENGAJAR PESERTA DIDIK DI KELAS VII M MTS AL-AMIRIYYAH - Nurul Hikmah, Deviya; Manshur, Ali (Jurnal PENEROKA: Kajian Ilmu Pendidikan Bahasa dan Sastra Indonesia, 2024)
This research aims to describe deviations (interference) from Indonesian language rules in the teaching and learning interactions of students at MTs Al-Amiriyyah class VII M. The focus of the research is: (1) What is the form of language interference in the social interactions of students at MTs Al-Amiriyyah ? (2) What are the types of language interference with students' social interactions at MTs Al-Amiriyyah? The qualitative descriptive method is the approach used in research on language interference. The techniques used in this language interference research are listening, engaging, speaking and taking notes. Data analysis used in this research is data reduction, data presentation, and conclusions. In accordance with the results of research that has been carried out, forms of Javanese language interference into Indonesian have been found from several aspects. Among other things, in terms of absorption elements, in terms of actors and in terms of fields. Apart from the forms of interference above, other types of Javanese language interference were also found at the linguistic level. These data are 17 phonological interference speech data, 5 morphological interference speech data, and 49 syntactic interference speech data.